2005
DOI: 10.1176/appi.ajp.162.5.1013
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Clozapine and Risperidone on Spatial Working Memory in Schizophrenia

Abstract: The differential effects of these medications on spatial working memory may be due to the anticholinergic effects of clozapine and prefrontal dopamine-enhancing effects of risperidone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 19 publications
(17 reference statements)
1
30
1
Order By: Relevance
“…There are some reports that CLZ can significantly improve working memory dysfunctions in schizophrenic patients (e.g., Grace et al 1996;Galletly et al 1997Galletly et al , 2005Sharma et al 2003), as opposed to several findings reporting no or even detrimental effects of chronic CLZ treatment on working memory performance in affected individuals (e.g., Hagger et al 1993;Lee et al 1999;Adler et al 2002;McGurk et al 2005). While there has been a long discussion on the involvement of hippocampal dysfunctions in the neuropathology and pathophysiology of schizophrenia (Harrison 1999(Harrison , 2004Weinberger 1999;Antonova et al 2004;Tamminga 2006), the nature and/or severity of hippocampal abnormalities are likely to differ considerably between individual subjects suffering from this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports that CLZ can significantly improve working memory dysfunctions in schizophrenic patients (e.g., Grace et al 1996;Galletly et al 1997Galletly et al , 2005Sharma et al 2003), as opposed to several findings reporting no or even detrimental effects of chronic CLZ treatment on working memory performance in affected individuals (e.g., Hagger et al 1993;Lee et al 1999;Adler et al 2002;McGurk et al 2005). While there has been a long discussion on the involvement of hippocampal dysfunctions in the neuropathology and pathophysiology of schizophrenia (Harrison 1999(Harrison , 2004Weinberger 1999;Antonova et al 2004;Tamminga 2006), the nature and/or severity of hippocampal abnormalities are likely to differ considerably between individual subjects suffering from this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Though some studies report a beneficial effect (McGurk et al, 2005), we previously reported in two independent samples a worsening of spatial working memory on an oculomotor-delayed response (ODR) task after risperidone treatment (Reilly et al, , 2007. The ODR task places heavier demands on maintenance rather than manipulation aspects of working memory compared to most neuropsychological tests, and therefore it is more similar in cognitive demand to the requirements of the predictive saccade task.…”
Section: Spatial Working Memorymentioning
confidence: 90%
“…In a more recent study, risperidone was found to improve spatial working memory compared with haloperidol; however, this superiority was eliminated when the confounding effects of the anticholinergic benztropine (administered adjunctively with haloperidol) were considered (McGurk et al, 2004). Other studies in subjects with schizophrenia have documented both improvements (McGurk et al, 2005) and impairments (Reilly et al, 2006) in spatial working memory associated with long-term risperidone treatment. The clinical effects of antipsychotics on sustained attention also appear to be equivocal.…”
Section: Discussionmentioning
confidence: 95%